Insertion of Umbilical Cord on Placenta in Hypertensive Mother (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Hypertensive disorders in pregnancy are responsible for significant amount of maternal and perinatal morbidity and mortality. This study was designed to see the association of umbilical cord insretion on placenta in hypertensive mothers. Objective: This purpose of the present stufdy was to find out the site of umbilical cord insertion on placenta in pregnancy associated with hypertension and to correlate it with the weight of the placenta and the condition of the newborn. Methodology: This descriptive cross-sectional study was conducted at the Department of Anatomy, Rajshahi Medical College and Department of Obstetrics & Gynaecology at Rajshahi Medical College & Hospital, Bangladesh. Placental weight, diameter, thickness, insertion site of umbilical cord, insertion percentage of the cord and weight of newborn were noted. The site of cord insertion was detected and insertion percentage was calculated with the help of d/r x 100. Results: A total 130 cases were selected for the study, 30 from normal, 33 from mild, 34 from moderate and 33 from severe hypertensive group respectively. The study demonstrated that mild to severe hypertension had smaller placentas with the tendency of deviation of umbilical cord towards the margin for insertion. Newborns of such mothers had low birth weight mostly; few of them had birth asphyxia.Conclusion: This study has been established that the marginal insertion of umbilical cord on placenta is associated with hypertension and severity of hypertension deviates the insertion site towards the margin.Journal of National Institute of Neurosciences Bangladesh, 2016;2(2): 89-93